(untitled) (RuMoRes, 2023)
The question of how to develop media critique and/or critiques in media in a scenario of new modes of circulation and appropriation has been made more urgent due to the acceleration of processes of mediatization. In this context, media critique and/or critiques in media have increasingly revolved around debates on the recognition of so-called minorities’ identities and differences. This study reflects on how media critique and/or critiques in media can be developed with these demands as a parameter. We contextualize these new modes of circulation and appropriation of the media and seek to investigate how recognition and identity gain importance for media critique and/or critiques in media, bringing as a corpus of analysis a social actor and his media explanations. At the end of our journey, we suggest methodological possibilities that may properly align with these (not so) new social demands.